Qualitative and quantitative agreement research on three diagnostic methods for maxillary transverse discrepancy - Zhang Ningbo; Wang Tianxiao; Yan Feng; Chen Rui; Fu Xinyu; Ren Liling (BMC Oral Health)
Abstract Objective The purpose of this cross-sectional study is to compare the agreement of three diagnostic methods for maxillary transverse deficiency (MTD) across different skeletal malocclusion. Methods Three hundred and sixty patients were categorized into skeletal classes I, II, and III based on the ANB angle and assessed using University of Pennsylvania analysis (UPA), Yonsei transverse analysis (YTA), and Andrews Element III analysis (AEA). The intraclass correlation coefficient (ICC) was used to evaluate quantitative agreement, while Cohen's kappa was used to measure qualitative agreement. Results In class I, the AEA showed moderate quantitative agreement with the UPA and AEA (ICC = 0.712), but the UPA and YTA had poor agreement (ICC = 0.404). Qualitatively, UPA and AEA were highly consistent (kappa = 0.896), while YTA and UPA (kappa = 0.371), YTA and AEA (kappa = 0.330) were poor uniformity. For class II, AEA and UPA showed moderate quantitative (ICC = 0.708) and high qualitative agreement (kappa = 0.917), while YTA's qualitative agreement with UPA (kappa = 0.550)/AEA (kappa = 0.544) was moderate. In class III, the AEA again had moderate quantitative agreement with the UPA (ICC = 0.657) and YTA (ICC = 0.580), but the agreement between the UPA and YTA is poor (ICC = 0.408). UPA and YTA were similar in qualitative agreement (kappa > 0.8), and both showed substantial agreement with AEA (kappa = 0.657). Conclusion 1. The incidence of MTD is highest in the skeletal class III group and the lowest in the skeletal class II group. 2. The results of YTA, AEA and UPA for diagnosing MTD are only consistent in patients with skeletal class III. In clinical practice, all three methods can be used to diagnose MTD in patients with skeletal class III malocclusion. 3. For patients with skeletal class I and class II malocclusion, it is recommended to use AEA and UPA for MTD diagnosis.